Implementasi Pelayanan Gender Sensitives Policing (GSP) Untuk Mengurangi Secondary Victimization Terhadap Korban kekerasan Pada Perempuan: di Direktorat PPA/PPO Polda Metro Jaya - Nur Nisfi Ardiansari; Ilham Prisgunanto (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2026)
This research focuses on the implementation of Gender Sensitive Policing (GSP) in reducing secondary victimization among female victims of violence at the Sub-Directorate of Women and Children Protection (PPA), Directorate of General Criminal Investigation, Polda Metro Jaya, particularly across service points including reporting, examination, case documentation (BAP), medical examination, and referrals. The research approach is qualitative using a case study method. Data collection techniques include interviews, non-intrusive observations, and document analysis involving investigators, female victims, unit leaders, and official documents (BAI/BAP) at the Sub-Directorate of PPA Polda Metro Jaya. The findings of this study indicate that GSP practices have been implemented in forms such as the use of specialized service rooms (RPK), victim assistance, gradual questioning techniques, provision of breaks during examination, and psychological referrals, which empirically help reduce victims’ psychological burden. However, secondary victimization persists within procedural aspects, particularly through repeated narration across multiple reports, highly explicit exploration of traumatic events, fragmented examination processes, and prolonged waiting periods experienced by victims. These findings suggest that GSP is more effective at the interactional level but has not been fully institutionalized within evidentiary and administrative procedures.